Theoretical, structural and in silico analysis of aminochalcones derivatives with potential antioxidant and anti-SARS-CoV-2 - Almeida Neto, Francisco Wagner de Queiroz (2021)
Due to the growing interest in the chemistry of the class of molecules called chalcones, these species demonstrate broad pharmacological applicability depending on the chemical nature of the groups attached to the A and B rings, the molecule N-{4'-[(E)-3-(4-fluorophenyl)-1-(phenyl)-prop-2-en-1-one]}-acetamide (PAAPF) was recently synthesized. The quantum chemical calculations were made for the complete theoretical characterization (structural, spectroscopic, electronic, and non-linear optical properties) applying three differents Density Functional Theory (DFT) methods such as B3LYP, mPW1PW91, and M06-2X with base set 6-311++G(d,p). After the characterization, the antioxidant activity was studied by the theoretical mechanisms using the different DFT methods. Then, using Molecular Docking calculations, six chalcones were studied as potential antivirals for inhibiting important enzymes of SARS-CoV-2 due to the health emergency of the COVID-19 pandemic and the search for antiviral candidates for a new disease, which until the present date, it does not have efficient treatment. All the three DFT methods used in this work can describe the PAAPF chalcone with great precision: the results of infrared spectroscopy and 1H and 13C isotropic shielding demonstrate to be in excellent agreement with the experimental data. The PAAPF chalcone can be used in optical devices due to its results for non-linear optical properties. Finally, the experimental data of antioxidant activity showed a moderate rate of reaction with the DPPH molecule (50.92%), and this fact was proven theoretically by the Hydrogen Atom Transfer (HAT) mechanism being the most favorable. Together, the results suggest that the PAAPF chalcone along with five others derivates N-{4'-[(E,E)-3-(phenyl)-1-(phenyl)-prop-2-en-1-one]}-acetamide named PAACN, N-{4'-[(E)-3-(phenyl)-1-(phenyl)-prop-2,4-dien-1-one]}-acetamide named PAAB, N-{4'-[(E)-3-(4-dimethylaminophenyl)-1-(phenyl)-prop-2-en-1-one]}-acetamide named PAAPA, N-{4'-[(E)-3-(4-ethoxyphenyl)-1-(phenyl)-prop-2-en-1-one]}-acetamide named PAAPE, and N-{4'-[(E)-3-(4-methoxyphenyl)-1-(phenyl)-prop-2-en-1-one]}-acetamide named PAAPM inhibit the virus interaction with human host cells through binding to the ACE2 or SPIKE protein, probably generating a steric impediment. In addition, chalcone molecules have an affinity for important enzymes in post-translational processes, interfering with viral replication.